# distance formula

posted by .

I need to find the distance between two points, (6,-3) and (-1,4).

d = sqrt[(x2-x1)^2 + (y2-y1)^2)]

I got that down to the sqrt of 98, which is the decimal 9.899494937, approximated at 9.9. Is this the right answer?

• distance formula -

d^2 = 7^2 + 7^2 = 49*2
d = 7 sqrt 2
d = 9.899 etc yes

• distance formula -

Thank you for taking the time to double check my work! God bless!

## Similar Questions

1. ### Geometry

How do I find the distance between (-9,3) and (-1,-5) By using the Pythagorean theorem. The line between the two points is the hypotenuse of a triangle with perpendicular side lengths of 8 in the x direction and 8 in the y direction. …
2. ### MATH

I need to simply this equation, but I got stuck. h/(4-sqrt(16+h)) = y First, I multiplied (4+sqrt(16+h)/(4+sqrt(16+h) to both sides, and I ended up with h(4+sqrt(16+h)/-h. Is this correct?
3. ### Geometry

Okay, this is a problem that I've tried over ten times before getting a fresh problem and trying that one too. I've never gotten a correct answer and I can't figure out why it's not right. Here's the problem, "Find the distance between …

Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
5. ### Math/Calculus

Solve the initial-value problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else?
6. ### trigonometry

find the values of y if the distance between the two points (10,y) and (16,2) is 10. i wrote down the distance formula: 10=SQRT(16-10)squared + (2-y)squared now how do i solve for y?
7. ### math-Inverse functions

f(x)=-4x-2 & g(x)=5x-6. Find (f*g) and state domain. f(x)-x^2-1 what is the equation for f^-1(x)?
8. ### Math

1.Find the distance between P(7, -4) and the line with equation x - 3y + 5 = 0 round to nearest tenth 3Y=x+5 y=(x+5)/3 -1/m = -3 y=-3x+b sub in P(7,-4) -4=-3(7)+b b=21-4 b=17 y=-3x+17 set the two equations equal. -3x+17=(x+5)/3 -9x+51=x+5 …